Conjectures and questions in convex geometry (of interest for quantum theory and other physical statistical theories) - Mana, P (2011)
Some conjectures and open problems in convex geometry are presented, and their physical origin, meaning, and importance, for quantum theory and generic statistical theories, are briefly discussed.